Implementasi Kurikulum Merdeka Pendekatan “Deep Learning” dalam Pembelajaran Ilustrasi Digital di SMA - Emil Tegar Salas Efendi; Setyo Yanuartuti; Welly Suryandoko; Indar Sabri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The Merdeka Curriculum at this time has carried a new approach, namely deep learning that focuses on three principles: full of awareness, meaningful, and encouraging. This paper aims to describe the implementation of the Independent Curriculum with a Deep Learning approach on digital illustration drawing materials at SMA Kemala Bhayangkari 1 Surabaya. The focus of the study is directed to the planning, learning process, and assessment applied by fine arts teachers in grade XII phase F. Writing uses a qualitative method with a case study approach through interview, observation, and documentation techniques. The results of the writing show that teachers have been able to translate the in-depth learning framework that includes the dimensions of graduate profiles, learning principles, learning experiences, and learning frameworks into digital illustration learning activities in a systematic manner. The learning plan is prepared through the determination of the element of